Rancangan Dan Implementasi Internet Provider Di Kos – Kosan Jakarta Barat Dengan Metode Load Balance Menggunakan Router D-Link Dan TP-Link - Yasmin Kamelia; Indra Cahya Firdaus (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The rapid advancement of technology causes the need for the use of internet access is getting higher, both for looking for the latest information, articles, and knowledge. Many boarding places that have integrated the internet network which becomes a facility in a boarding house. One of them is Sakinah Kos which is in West Jakarta, which is a boarding house that is located near with offices, as well as the average enthusiast is an employe and during a pandemic like these ALL-work processes are done in Work From Home (WFH) which causes the use of internet connection in Sakinah Kos to be overloaded and unstable due to too much I have a high internet connection. Because there are many complaints about unstable internet connection. So that way Sakinah Kos provides a solution to use tho ISPs and then use the load balancing method as internet network stability the mechanism is that the load balancer will mark the package that wants to access the internet, and then choose which ISP path will cross and equalize the load on both ISPs.